1984
DOI: 10.1172/jci111500
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transport in the rabbit superficial proximal convoluted tubule.

Abstract: Abstract. Calcium transport was studied in isolated S2 segments of rabbit superficial proximal convoluted tubules. '"Ca was added to the perfusate for measurement of lumen-to-bath flux (JibCa), to the bath for bath-to-lumen flux (JbIc), and to both perfusate and bath for net flux (Jnetc). In these studies, the perfusate consisted of an equilibrium solution that was designed to minimize water flux or electrochemical potential differences (PD). Under these conditions, JibCa (9.1 ± 1.0 peq/mm min) was not differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 41 publications
5
28
0
1
Order By: Relevance
“…Micropuncture studies have found that about 60% of filtered Ca2+ is reabsorbed in segment 1 and 2 of the proximal convoluted tubule, and 10% in the proximal straight tubule [13 ,17, 31]. It has been proposed that nearly all Ca2+ absorption in these tubules is passive and occurs via the paracellular route [1,5,21]. The present findings in segment 2 and 3 of the proximal tubules support the paracellular pathway of Ca2+ absorption.…”
Section: Localization Of Ca2+in Nephronssupporting
confidence: 74%
“…Micropuncture studies have found that about 60% of filtered Ca2+ is reabsorbed in segment 1 and 2 of the proximal convoluted tubule, and 10% in the proximal straight tubule [13 ,17, 31]. It has been proposed that nearly all Ca2+ absorption in these tubules is passive and occurs via the paracellular route [1,5,21]. The present findings in segment 2 and 3 of the proximal tubules support the paracellular pathway of Ca2+ absorption.…”
Section: Localization Of Ca2+in Nephronssupporting
confidence: 74%
“…Recently, Worcester and colleagues (50) demonstrated that in individuals with hypercalciuria the proximal tubule inappropriately failed to reabsorb Ca 2ϩ filtered by the glomerulus. Ca 2ϩ is reabsorbed from the proximal tubule via a passive paracellular process, with the active transcellular flux of sodium (Na ϩ ) serving as the driving force (35,37). Under conditions of normal dietary Ca 2ϩ content, the majority of ingested Ca 2ϩ is absorbed from the small intestine by a similar process (28).…”
Section: Camentioning
confidence: 99%
“…The bulk of Ca2" reabsorption in this segment parallels the reabsorption of Na+, such that tubular fluid (TF) to plasma ultrafiltrate (UF) TF/UFNa+/TF/ UFca2+ concentration is nearly a unity under nondiuretic conditions (1,2). In situ microperfusion experiments demonstrate high permeability to Ca2+ in this segment, such that the unidirectional effilux of Ca2+ is 2-3 times larger than the net flux (3)(4)(5). These observations have been interpreted to indicate that the bulk of Ca2' reabsorption in the proximal convoluted tubule is a passive process, and some investigators (6) have speculated that a paracellular Ca2+ flux through the tight junctions is the major path of Ca2' reabsorption in the proximal convoluted tubule.…”
mentioning
confidence: 97%